Penggunaan media pembelajaran digital dalam meningkatkan minat belajar siswa pada mata pelajaran fikih di madrasah aliyah ma’arif nu 1 bantarkawung - Siti Lutpiatul Marpuah; Edi Susanto; Euis Siti Nurjanah; Nur Alifah Agustin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The development of digital technology has brought significant changes in the world of education, including in Islamic Religious Education (IS). This study aims to analyze the use of digital learning media in increasing student interest in fiqh at Madrasah Aliyah Ma'arif NU 01 Bantarkawung. The study used a qualitative approach with a case study method. Data were obtained through interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that digital learning media plays an important role in increasing student enthusiasm, activeness, and interest in fiqh learning. The use of various digital media such as learning videos, interactive presentations, online learning platforms, and educational applications can create a more interesting and communicative learning atmosphere. Supporting factors for the implementation of digital media include the availability of technological facilities and teacher competence in utilizing digital media, while inhibiting factors include limited internet access, differences in students' technological abilities, and limited supporting devices. This study confirms that the use of digital learning media can be an effective strategy in increasing student interest in fiqh.